Mapping the Interconnections Between Somatic Complaints, Mentalization and Stress Coping in Young Adulthood: A Network Analysis Approach - Treigytė, Aistė; Mikučionytė, Dovilė; Adler, Asta (Psichologija, 2025)
Somatic complaints are highly prevalent among young adults and can significantly impair both psychological well-being and physical functioning. This study aimed to examine the associations between somatic complaints, mentalization, and stress coping strategies in young adults, a triad that remains underexplored in the current literature. A sample of 115 individuals (49 men, 66 women) aged 18–29 years completed an online survey assessing somatic complaints (Giessen Subjective Complaints List-24), mentalization (The Mentalization Scale, Dimitrijević et al., 2018), and stress coping strategies (Lithuanian Coping with Stress Questionnaire – Revised, Valickas et al., 2010). A network analysis approach was used to explore the complex interconnections among these constructs. Findings revealed that motivation to mentalize and self-oriented mentalization were the most central variables in the network, highlighting their importance in regulating stress and somatic symptoms. Notably, lower self-mentalization was strongly associated with greater somatic complaints and the use of maladaptive coping strategies. Somatic symptoms formed a densely connected subnetwork, with emotional venting emerging as the strongest directly linked maladaptive strategy. Conversely, adaptive coping strategies were positively associated with various dimensions of mentalization and appeared to buffer the impact of stress on somatic health. These results underscore the importance of self-reflective and motivational components of mentalization, as well as adaptive coping, in understanding and addressing somatic complaints. Enhancing these factors may offer promising therapeutic targets for interventions to reduce somatic symptom burden in young adults.